Pemimpin dan Kepemimpinan: Total Quality Management (TQM) Kepemimpinan dan Kerja Sama Tim dalam Pendidikan Islam - Fazrurrakhman Al Farisi; Encep Syarifuddin; Saefudin Zuhri (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This article deals with implementing Total Quality Management (TQM), leadership, and organization in Islamic education. The author explained that TQM could help improve the quality of Islamic education by supporting continuous quality control. Also, good leadership is needed to support the implementation of TQM in Islamic educational institutions. Furthermore, the authors explain that teamwork is important in implementing TQM in Islamic educational institutions. At the academic level, working together allows for better program development, greater community involvement, and better achievement of the company's mission and vision. This study uses a library research method that uses the literary method, that is, collecting data from different types of good books and using qualitative research methods. Finally, the authors concluded that integrating TQM, leadership, and teamwork can help improve the quality of Islamic education. However, the authors emphasize that successful implementation requires awareness and involvement of all stakeholders, as well as effective and sustainable management.